Penerapan Metode Building Information Modeling (BIM) Pada Pembangunan Gedung Integrated Laboratory for Natural Science and Food Technology Universitas Jember - Agam Risza Adhitama; Anik Ratnaningsih; Willy Kriswardhana (Universitas Jember, 2021)
Universitas Jember built high rise building and had a high complexity of work, it requires a construction project management to simplify and minimize errors in its process. Project management performance can be described through the concept of Building Information Modeling (BIM). The application of BIM method in this study used Revit Architecture for software support to obtain volume at each job in the monitoring process to determine MC0 and termin setting processes. The data used namely shop drwaning / forcon which is used as a reference in model. Building modeling in this study is divided into 3 modeling phases, namely lower structure modeling, upper structure and architecture. Based on the model, a tie beam volume was 26.74 m3 with reinforcement was 4,361 kg, 1st floor column concrete modeling was 52.87 m3 with reinforcement was 12.176,39 kg and perimeter wall volume on the 1st floor was 320.71 m2. The error that appeared in the calculation of the concrete volume in the BIM modeling with the conventional method is 0% while the error that appears in the reinforcement calculation is 0-0.042%.